Virtualisation of Network Functions and the SDN: Improving the Economics of the Network - Iyer, Sundar (Journal of Telecommunications and the Digital Economy, 2014)
A 'telco' or telecommunications service provider’s network is both the source of its high cost base and source of differentiation. Telcos incur the high capital and operational costs of customised, vendor-proprietary hardware as they seek differentiation through network capacity addition, service quality and coverage improvement. These decisions to invest in the network are motivated by supply-side competition and demand particularly cross-segment demand for data services, much of which is for ‘over-the-top’ social networking and video streaming services that the telco can only partially monetise. This has created a dichotomy of margin erosion a high cost to serve with diminishing returns on additional capacity investments. However, an approach that blends IT, networking and data centre technologies promises to improve this equation, as evidenced by primary research, surveys and proof-of-concepts by Hewlett Packard. Network Functions Virtualisation (NFV) offers to immediately lower the capital and operational cost base by implementing a growing set of previously closed network platforms and functions on standard IT hardware. This will set the scene in the next few years for faster software-defined network (SDN) additions which will improve utilisation of network assets and allow lower-cost experiments to flex and scale capacity to improve network services and introduce new innovations. This article provides an introductory view of these emergent developments.